Model Pembelajaran Multikultural Berbasis Refleksi di Era Digital - Agustian, Murniati (Antroposen: Journal of Social Studies and Humaniora, 2022)
The purpose of this research is exploring the reflection of prospective of elementary school teachers on the multicultural learning model by using the Qualitative Method. The student’s reflections focus on materials, methods, media and learning assessments. The method used is content analysis of each student's reflection in two semesters and unstructured interviews to confirm the reflection. The results of this research show that the identity of material is considered important, it is because the human has many identities, not only single identity. In the learning process used the method to make the analogy of the images or the objects that upload on Moodle, and then get the comments by peers. This method seems to be able to increase self-esteem and respect of other people who had different identity. Film discussions about sensitive topics that’s get from YouTube also able to make students think critically, assertive, and agree to disagree, so then the conflicts do not need to be occur. Learning about the local wisdom such the Baduy tribe through movie of Baduy also can increase the respect to the Baduy tribe, respect to the culture of students themselves, and eliminate prejudice of stereotypes. In conclusion, in the digital era learning models with various methods, various media, and reflection-based assessments can develop the character of respecting differences in a multicultural society. As prospective teachers, students are inspired to apply when they become teachers.